The terms "veils of knowledge" in the Holy Qur'an: A linguistic and semantic study - Aziz Jabr , Lect . Dr. Maytham (Basra studies journal, 2025)
The researcher objectively examined the terms "veils of knowledge" in the Holy Quran from a linguistic and semantic perspective. The research is divided into two sections: the first: the linguistic and interpretive meanings of the terms "veils of knowledge" and the relationship between them; the second: the linguistic differences between the meanings of the terms "veils of knowledge." I adopted the descriptive-inductive approach to examine the views of linguists and interpreters, and the comparative approach to distinguish between the linguistic and interpretive meanings. The research reached the most important conclusions: The Quran expresses the obstacles that prevent people from finding the path of truth in various terms. These terms share a general meaning, namely "obstruction," but differ in subtle linguistic nuances, while taking into account the appropriateness of the context of the Quranic text, which is consistent with each term.